O sistema de proteção ao consumidor e os grandes conglomerados comerciais – reflexões interdisciplinares - Vieira, Ariostenis Guimarães (Universidade Federal do Tocantins, 2016)
This work takes advantage of interdisciplinarity to analyze the challenges to the realization of human rights since the struggles that led to the French Revolution and the construction of the first declarations of Human Rights to the present day where the judiciary is increasingly being depositary of the expectations and hopes of democratic societies. To this end, it sought from the start to bring the right visions not only legal on the subject, just to give dynamism to the process of knowledge and as it comes to a professional master's degree, qualify the technical improvement. For a better understanding of the struggles and contradictions of the construction process of human rights by inserting them in the economic and social context of capitalism, sought to bring the legal debate the view of history, philosophy and sociology. The result of this complex interaction of knowledge is the overcoming of value neutrality that both sought to mark the formation and performance of legal professionals.